Maintenance of the paraspinal muscles may protect against radiographic knee osteoarthritis - Azuma K (Dove Medical Press, 2017)
Koichiro Azuma,1 Yasushi Sera,1 Takuma Shinjo,1 Michiyo Takayama,2 Eisuke Shiomi,2 Suketaka Momoshima,2 Yasushi Iwao,2 Hiroyuki Ishida,3 Hideo Matsumoto1 1Institute for Integrated Sports Medicine, Keio University School of Medicine, 2Center for Preventive Medicine, Keio University Hospital, Shinjuku-ku, Tokyo, 3Sports Medicine Research Center, Keio University, Kohoku-ku, Yokohama, Kanagawa, Japan Background: Knee osteoarthritis (OA) is an increasing health problem worldwide. So far, only obesity and quadriceps weakness are identified as modifiable risk factors for knee OA. Core muscle strengthening is becoming increasingly popular among older adults because of its ability to enhance the activities of daily living during old age. This study investigated the associations of the size and quality of the abdominal trunk muscles with radiographic knee osteoarthritis (RKOA). Methods: From 2012 to 2016, data were collected from 146 males and 135 females (age 63.9±13.4 years, BMI 23.2±3.8 kg/m2) at annual musculoskeletal examinations, including knee radiographs and body composition analyses, by dual-energy X-ray absorptiometry. Cross-sectional areas of abdominal trunk muscles were measured using a single-slice computed tomography scan image obtained at the level of the umbilicus. Results: The prevalence of RKOA was 21.2% in males and 28.1% in females. Compared to subjects without RKOA, subjects with RKOA were ~6 years older and had smaller paraspinal muscle (38.4±8.7 vs 33.1±10.1 cm2, p<0.01 in males; 24.1±7.1 vs 20.7±7.5 cm2, p<0.05 in females). In contrast, there was no decrease in appendicular or total lean mass, and only in females, BMI and total fat mass (FM) were higher in subjects with RKOA (21.5±3.5 vs 24.5±4.4 kg/m2, 16.7±7.0 vs 20.5±7.7 kg, respectively, both p<0.01). After adjusting for age and sex, smaller cross-sectional area/lower attenuation value of the paraspinal muscles was associated with RKOA (both p<0.05), while greater appendicular or total lean mass as well as greater FM was associated with RKOA. The size and quality of the paraspinal muscles were not associated with knee pain or habitual exercise. Conclusion: Small, poor-quality paraspinal muscles may be linked to a higher risk of RKOA, but appendicular or total lean mass was not a good predictor of RKOA. Keywords: radiographic knee osteoarthritis, paraspinal muscle cross sectional area, paraspinal muscle attenuation, lean body mass, fat mass